STUDY OF KUNDALIKA RIVER WATER POLLUTION, SOURCES AND EFFECT ON HUMAN HEALTH IN ROHA TALUKA, DIST.RAIGAD, MAHARASHTRA, INDIA (International Journal of Food and Nutritional Sciences, 2022)
Pollution of rivers in India is continuously affecting many areas and affecting the human and environment. Due to changes in the quality standards of river water, the quality of river water is changing and now it is no longer potable. Pollution of river water is affecting the ecosystem of the river. People are facing health related problems due to the consumption of contaminated water from the river. Four water samples of Kundalika river were collected from Kolad bridge side, Killa village side , Roha bridge side, Dhatav nala side. These water samples were collected during the month of May-June 2022 from each site and analysed for its physic-chemical parameters with respect to its water pollution, sources and effect on human health. The overall parameters observed in the study area showed that the water of Kundlika River is suitable for irrigation and domestic use only and not for drinking purpose. River pollution is a growing problem in Roha region today, so the factors which polluting the river need to be controlled. Therefore, it is important to protect river water by frequent monitoring and inspections of water quality to reduce human activities in this region.